Order acceptance and scheduling: overview and complexity results. (2019) - Palakiti, Venkata Prasad; Mohan, Usha; Ganesan, Viswanath Kumar
The order acceptance and scheduling (OAS) problem is an important aspect of the manufacturing process, especially when production is carried out on a made-to-order basis with stringent deadlines and limited production capacity. This paper provides an overview of existing OAS problems by considering due date related dimensions in deterministic scenarios. A three-field notation was introduced for classifying OAS problems, and reviewing solution algorithms and complexity results for the same. This research effort proved the complexity results for existing, open as well as new OAS problems with due dates, and additionally, outlined the complexity results for newly defined OAS problems without due date dimensions.